Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có:(7x-11)3=25 * 52 + 200
=> (7x-11)3=32 * 25 + 200
=> (7x-11)3=800 + 200
=> (7x-11)3=1000 = 103
=> 7x-11 = 10
=> 7x = 21
=> x = 3
(7x - 11 )^3 = 32*25+200
(7x - 11 ) ^3 = 1000
(7x-11)^3 = 10^3
=> 7x - 11 = 10 => 7x = 11 + 10 = 21 => x = 21 : 7 => x = 3
( 7x - 11 )3 = 32 . 25 + 200
( 7x - 11 )3 = 800 + 200
( 7x - 11 )3 = 1000
( 7x - 11 )3 = 103
=> 7x - 11 = 10
7x = 10 + 11
7x = 21
x = 21 : 7
x = 3
\(\left(7x-18\right).3=2^5.5^2+200\)
\(\Rightarrow\) \(\left(7x-18\right).3=32.25+200\)
\(\Rightarrow\) \(\left(7x-18\right).3=800+200\)
\(\Rightarrow\) \(\left(7x-18\right).3=1000\)
\(\Rightarrow\) \(7x-18=\frac{1000}{3}\)
\(\Rightarrow\) \(7x=\frac{1054}{3}\)
\(\Rightarrow\) \(x=\frac{1054}{21}\)
\(6^{x-2}\) :12 =3
\(6^{x-2}\) = 3.12
\(6^{x-2}\) = 36
\(6^{x-2}\) = \(6^2\)
⇒ x - 2 =2
x = 2+ 2
x = 4
Vậy x =4
3 + \(2^{x-1}\) = 24 - [\(4^2\) - (\(2^2\) -1)]
3 + \(2^{x-1}\) = 24 - [16 - (4-1)]
3 + \(2^{x-1}\) = 24 - (16 - 3)
3 + \(2^{x-1}\) = 24 - 13
3 + \(2^{x-1}\) = 11
\(2^{x-1}\) = 11-3
\(2^{x-1}\) = 8
\(2^{x-1}\) = \(2^3\)
⇒ x - 1 = 3
x = 3 + 1
x = 4
Vậy x = 4
\(\left(7x-11\right)^3\) = \(2^5.5^2+200\)
\(\left(7x-11\right)^3\)\(\left(7x-11\right)^3\)
\(\left(7x-11\right)^3=2^5\times5^2+200\)
\(\left(7x-11\right)^3=32\times25+200\)
\(\left(7x-11\right)^3=800+200\)
\(\left(7x-11\right)^3=1000\)
\(\left(7x-11\right)^3=10^3\)
\(\Rightarrow7x-11=10\)
\(7x=10+11\)
\(7x=21\)
\(x=21\div7\)
\(x=3\)
(7x-11)^3=2^5x5^2+200
(7x-11)^3=32x25+200
(7x-11)^3=800+200
(7x-11)^3=1000
(7x-11)^3=10^3
=>7x-11=10
7x=10+11
7x=21
x=21:7
x=3
Bài này nhiều người hỏi rồi nha
\(\left(7x-12\right)^2=2^5.5^2+200\)
\(\left(7x-12\right)^2=25.32+200\)
\(\left(7x-12\right)^2=800+200\)
\(\left(7x-12\right)^2=1000=\left(10\sqrt{10}\right)^2\)
\(\Leftrightarrow\left[{}\begin{matrix}7x-12=10\sqrt{10}\\7x-12=-10\sqrt{10}\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{10\sqrt{10}+12}{7}\\x=\dfrac{12-10\sqrt{10}}{7}\end{matrix}\right.\)